Women’s Resistance to Male Authority in Madurese Song Lyrics - D. Dzarna; Astri Widyaruli Anggaraeni; Shaya Seriefaza; Ichtiar Syahru Ramadhan (RETORIKA: Jurnal Ilmu Bahasa, 2026)
This research aims to unravel women’s resistance against male authority in Madurese song lyrics. This research is motivated by the limited number of studies examining women’s resistance to men through songs, which are a subtle yet powerful form of cultural expression. Madurese songs serve as a symbolic space for women to express their experiences, injustices, and critiques of gender relations. This study focuses on linguistic elements that contain open resistance, namely relational modality, negative diction, metaphors, and personal pronouns. The method employed is qualitative, utilizing Norman Fairclough's critical discourse analysis approach. The data source for this research is Madurese songs focusing on themes of polygamy, infidelity, and romance. The data are derived from the lyrics of Madurese songs. The findings reveal linguistic elements containing open resistance (public transcript), including relational modalities, negative diction, metaphors, and personal pronouns. Linguistic elements containing resistance are employed in Madurese song lyrics because Madurese women do not receive justice and do not want to be marginalized by male authority. From a feminist perspective, Madurese songs represent women’s negotiation of unequal power relations. Thus, Madurese women are not entirely naive; rather, they have their own ways of resisting, maintaining their dignity, and building awareness of their position within the social structure.